1998
DOI: 10.1002/(sici)1098-108x(199811)24:3<319::aid-eat10>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Body image dissatisfaction and eating attitudes in visually impaired women

Abstract: Objective The high levels of body dissatisfaction and abnormal eating attitudes currently prevalent in Western societies have been attributed by many authors to the promotion of an unrealistically thin ideal for women. We investigated the role of the visual media by examining the relationship between body image dissatisfaction and eating attitudes in visually impaired women. Method: Questionnaires were administered to 60 women, 20 congenitally blind, 20 blinded later in life, and 20 sighted. Results: Congenita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 9 publications
1
20
0
1
Order By: Relevance
“…On the contrary, women had a higher prevalence of positive BID compared to men - 265 (65.0%) vs. 93 (24.7%) respectively. This is in contrast to other literature on this topic which shows that body image dissatisfaction (assumed to be negative only) is more prevalent in women than men [42-45]. In fact, according to a study conducted in America, many contemporary American women covet an unrealistically thin body build for themselves, a phenomenon that could be detrimental to their emotional and physical health [5].…”
Section: Discussionmentioning
confidence: 83%
“…On the contrary, women had a higher prevalence of positive BID compared to men - 265 (65.0%) vs. 93 (24.7%) respectively. This is in contrast to other literature on this topic which shows that body image dissatisfaction (assumed to be negative only) is more prevalent in women than men [42-45]. In fact, according to a study conducted in America, many contemporary American women covet an unrealistically thin body build for themselves, a phenomenon that could be detrimental to their emotional and physical health [5].…”
Section: Discussionmentioning
confidence: 83%
“…A follow-up study showed that this trend continued between 1979 and 1988: Miss America contestants continued to become thinner, and Playboy centrefolds fell into a plateau of very low BMIs (Wiseman, Gray, Mosimann, & Ahrens, 1992). Others have examined body satisfaction and eating disorder symptamology as correlates of use of mass media (e.g., Abramson & Valene, 1991;Baker, Sivyer, & Towell, 1998;Cash, Cash, & Butters, 1983;Posavac, Posavac, & Weigel, 2001), the idea being that the mass media promulgate a slender ideal that elicits negative affect. Thus, the preference for relatively slender ideals in industrialised settings in the current study may be traced back to the emphasis on a slim physique and negative stereotyping of obese figures (Becker & Hamburg, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Although they choose the ectomorphic (thin) body build as ideal, most women report that they have a more mesomorphic (muscular) build (Spillman & Everington, 1989). Confirming the role of the visual in perceptions of body image (albeit not necessarily media influence), women who are blind, or partially blind, are significantly less likely than sighted women to express body dissatisfaction and to display disordered eating attitudes (Baker, Sivyer, & Towell, 1998). Posavac, Posavac, and Posavac (1998) …”
Section: Body Satisfaction In Femalesmentioning
confidence: 97%